2020
DOI: 10.1016/j.heliyon.2020.e04523
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of a crossflow turbine for Pico hydropower electricity generation

Abstract: This study covered the design, implementation and performance evaluation of a crossflow turbine at various nozzle positions. The chosen blade material was analyzed using ANSYS for stress and deformation degree under the impact of hydraulic jets to ascertain its suitability while in operation. The shaft was analyzed under static and dynamic conditions using ANSYS in order to ensure a non-plastic deformation of the shaft at both conditions. The outcome of this analysis was employed in the harmonic response analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…One of the significant considerations in the design of a runner is the determination of the optimum number of blades. Studies have shown that the first stage does not transform all the available energy into power [55,56]. The squirrel-cage blower form of CFT enables the water to flow across the blades twice.…”
Section: The Number Of Rims and Bladesmentioning
confidence: 99%
“…One of the significant considerations in the design of a runner is the determination of the optimum number of blades. Studies have shown that the first stage does not transform all the available energy into power [55,56]. The squirrel-cage blower form of CFT enables the water to flow across the blades twice.…”
Section: The Number Of Rims and Bladesmentioning
confidence: 99%
“…The nozzle distance was very close to the runner shaft, the angle of attack was lower, and the nozzle height was chosen to maximize energy transfer to the upper and lower blade profiles. These factors all contributed to the highest turbine performance as well [15]. The advantages of the breastshot type include higher efficiency compared to undershot type, shorter fall height compared to overshot type, and can be applied to a uniform flow of water sources [16].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The pico-hydro-based off-grid-type crossflow turbine is a suitable option to increase the electrification ratio in remote areas. A crossflow turbine (CFT) is an economical turbine since it has a simple shape and can operate even when there are high flow-rate fluctuations (meaning it can be applied in run-of-river conditions) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%